The use of heart rates and graded maximal test values to determine Rugby Union game intensities - Sparks, M.; Coetzee, B. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to determine the intensities of university rugby union games using heart rates and graded maximal test values. Twenty-one rugby players performed a standard incremental maximal oxygen uptake (VO2max) test to the point of exhaustion in the weeks between 3 rugby matches. The heart rates that corresponded to the first and second ventilatory thresholds were used to classify the heart rates into low-, moderate-, and high-intensity zones. The heart rates recorded through heart rate telemetry during the matches were then categorized into the different zones. The average heart rates for the different intensity zones as well the percentages of the maximum heart rate (HRmax) were as follows: low, 141-152 b/min (76.2-82.0% HRmax); moderate, 153-169 b/min (82.7-91.4% HRmax); and high, 170-182 b/min (91.9-100% HRmax). The percentages of time players spent in the different intensity zones were as follows: 22.8% for the low-intensity, 33.6% for the moderate-intensity, and 43.6% for the high-intensity zones. The dependant t-test revealed significant differences (p < 0.05) between the low- and high-intensity zones for the second halves, between the low- and moderate- as well as between the low- and high-intensity zones for the matches overall. To conclude, the results of the study showed that the above-mentioned method can be used to determine the intensities of university rugby union games. It also revealed that university rugby games are categorized by significantly more high-intensity activities than was previously reported by other rugby match analyzing-related studies. Thus, sport scientists and conditioning coaches should concentrate more on high-intensity activities for longer periods during training sessions.